2012
DOI: 10.1590/s0100-879x2012007500021
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic effects of repeated treatment with an essential oil from Lippia alba and (R)-(-)-carvone in the elevated T-maze

Abstract: Lippia alba (Mill.) N.E. Brown (Verbenaceae) is widely used in different regions of Central and South America as a tranquilizer. The plant's anxiolytic properties, however, merit investigation. The present study evaluated the effects of repeated daily (14 days) intraperitoneal (ip) treatment with an essential oil (EO) from a chemotype of L. alba (LA, chemotype II, 12.5 and 25 mg/kg; N = 6-8) and (R)-(-)-carvone (25 mg/kg; N = 8-12), the main constituent of this chemotype, on male Wistar rats (weighing 250 g at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 18 publications
1
33
0
2
Order By: Relevance
“…Nevertheless, further investigations are needed to determine if the essential oil of Lippia alba can be useful in pathological anxiety. Besides, other studies found that L. alba essential oil (carvone chemotype) show anxiolytic effect in rats, pointing that carvone could be responsible for its action as a tranquilizer, due to its effect as a depressor of the central nervous system, interacting with GABA A receptors in the brain after crossing the blood-brain barrier [19]. Therefore, carvone attenuate neurons in limbic and septo-hippocampal systems, structures involved in suppressing the response of "active-avoidance" [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, further investigations are needed to determine if the essential oil of Lippia alba can be useful in pathological anxiety. Besides, other studies found that L. alba essential oil (carvone chemotype) show anxiolytic effect in rats, pointing that carvone could be responsible for its action as a tranquilizer, due to its effect as a depressor of the central nervous system, interacting with GABA A receptors in the brain after crossing the blood-brain barrier [19]. Therefore, carvone attenuate neurons in limbic and septo-hippocampal systems, structures involved in suppressing the response of "active-avoidance" [34].…”
Section: Discussionmentioning
confidence: 99%
“…Its essential oil has several chemotypes depending on the geographic location and the characteristics of the soil and climate [14,15]. Different laboratories have determined the antibacterial [16], antifungal [17], anesthetics [18], and anxiolytic [19] effects of L. alba EOs.…”
mentioning
confidence: 99%
“…N.E. Brown, [21] but recently the oil of Lippia alba too appears to have antispasmodic effects on the gut. [22] Notably, the present findings were obtained using a dose of the enantiomers (100 mg/kg) that was administered orally, and this dose was considerably less than the LD 50 of 484 mg/kg and 426 mg/kg for (S)-(+)-carvone and (R)-(-)-carvone, respectively, that was administered intraperitoneally.…”
Section: Resultsmentioning
confidence: 99%
“…The data indicated that some plants have more diversified medicinal uses or applications than others [35]. Among all plants, Lippia alba with RI=2 was the most versatile species in relation to its use and has often been reported in ethnobotanical studies [36] and pharmacological use, for example, vasorelaxant effect [37], action as a tranquilizer [38] and effective at preventing gastric ulceration [39]. However, when the objective is the search for new plant-derived drugs, the concordance of the answers as to the medicinal use of a particular plant is extremely important.…”
Section: Use and Efficacy Of The Medicinal Plantsmentioning
confidence: 99%